2016
DOI: 10.2399/jmu.2016001001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of functional surgery for attic cholesteatoma

Abstract: Since the first description of atticoantrotomy in 1889, by Küster, numerous successful surgeries for attic cholesteatoma have been conducted. [1] New and more functional approaches to the eradication of cholesteatoma have arisen from a better understanding of the possible differences in the biological effects of cholesteatoma in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A smaller study by Çetinkaya et al reported the results of 30 patients with various types of mastoidectomies as follows: 85% hearing gain of 5-35 dB, 10% hearing loss and 3% status quo ante ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller study by Çetinkaya et al reported the results of 30 patients with various types of mastoidectomies as follows: 85% hearing gain of 5-35 dB, 10% hearing loss and 3% status quo ante ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Functional results of the surgery were still a future concern, and the patient was considered fortunate to survive the suppurative mastoiditis and only lose the sense of hearing to the affected ear. In the 19th century, Küster & Bergmann (1891) were equally credited with describing the first radical mastoidectomy and from there the surgical technique began its development ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%